2013
DOI: 10.1103/physrevd.88.044016
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave constraints on the shape of neutron stars

Abstract: We show that there is a direct relation between upper limits on (or potential future measurements of) the m = 2 quadrupole moments of slowly rotating neutron stars and the l = m = 2 deformation of the star's surface, in full general relativity, to first order in the perturbation. This relation only depends on the star's structure through its mass and radius. All one has to assume about the star's constituents is that the stress-energy tensor at its surface is that of a perfect fluid, which will be true with go… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…This is still the maximum observed spin-up for any globular cluster pulsar. 164 For this we have assumed a 1.4  M star and used approximate scalings calculated from Table 1 of Johnson-McDaniel (2013), taking into account that the rotational deformation scales with f rot 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is still the maximum observed spin-up for any globular cluster pulsar. 164 For this we have assumed a 1.4  M star and used approximate scalings calculated from Table 1 of Johnson-McDaniel (2013), taking into account that the rotational deformation scales with f rot 2 .…”
Section: Discussionmentioning
confidence: 99%
“…When the spin-down limit is not surpassed, no power ratio,˙Ė E gw , is given. a This is the equivalent upper limit on the = = l m 2 surface deformation maximized over the equation of state and stellar mass (Johnson-McDaniel 2013). Values below 10 are rounded to the nearest integer, values between 10 and 1000 are rounded to the nearest decade, and values above 1000 are rounded to the nearest hundred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…maximum stress, which the elastically deformed crustal material can withstand). If the crust is indeed as strong as it is suggested by molecular dynamic (MD) sim-⋆ E-mail:baiko@astro.ioffe.ru † E-mail:andr@astro.ioffe.ru ulations (Horowitz & Kadau 2009;Chugunov & Horowitz 2010, the GW emission can be poweful enough to be detectable by existing GW observatories (Johnson-McDaniel 2013;Caplan & Horowitz 2017). Haskell & Patruno (2017) have recently suggested that this GW emission could be responsible for observed spin-down during the accreting phase of PSR J1023+0038.…”
Section: Introductionmentioning
confidence: 99%
“…Second and third columns: Median of the 95% confidence level UL on the GW amplitude h 0 and corresponding ellipticity ϵ. Fourth column: Surface deformation corresponding to the median ellipticity for a NS with radius of 10 km[53]. Fifth column: Ratio between the median UL and the spin-down limit.…”
mentioning
confidence: 99%